Living with emergency. Design for an adaptive settlement in Belén, Iquitos - Belen Desmaison; Linda Buondonno; Giulia Viola; Andrea Giachetta (Agathón)
This paper presents a design for a district of the city of Iquitos, developed based on research by the Pontificia Universidad Católica del Perú and supported by the Centro Interuniveristario de Desarollo Academico exchange programme. The case study’s interest is in the conditions of environmental stress to which the district is subject due to seasonal variations in the water level of the river that runs through it. Under these circumstances, the inhabitants have spontaneously developed resilient settlement strategies which, however, are not sufficient to deal with the serious health and sanitary problems that exist there. The paper demonstrates how, in such situations, it is possible to propose adaptive design solutions which are in keeping with local practices and therefore easily reproducible.